Antiplatelet Premedication for Stent-Assisted Coil Embolization of Intracranial Aneurysms: Low-Dose Prasugrel vs Clopidogrel. Issue 5 (29th December 2017) - Choi, Hyun Ho; Lee, Jung Jun; Cho, Young Dae; Han, Moon Hee; Cho, Won-Sang; Kim, Jeong Eun; An, Sang Joon; Mun, Jong Hyeon; Yoo, Dong Hyun; Kang, Hyun-Seung
Abstract: BACKGROUND: The use of antiplatelet medications to prevent thrombosis in the treatment of cerebral aneurysms with stents has become widely emphasized. OBJECTIVE: To compare low-dose prasugrel with clopidogrel in stent-assisted coil embolization of intracranial aneurysms. METHODS: This is a retrospective review of 311 aneurysms from 297 patients who underwent stent-assisted endovascular coil embolization of unruptured intracranial aneurysm between November 2014 and March 2017. Thromboembolic and hemorrhagic adverse events were compared between 207 patients who received low-dose prasugrel (PSG group) and 90 patients who received clopidogrel (CPG group). RESULTS: P2Y12 reaction unit (PRU) values were significantly lower in the PSG group (PSG group vs CPG group, 132.3 ± 76.9 vs 238.1 ± 69.1; P < .001); the percentage of inhibition was also statistically higher in the PSG group (54.0 ± 26.0% vs 20.8 ± 18.6%; P < .001). Thromboembolic events occurred less frequently in the PSG group than in the CPG group (0.9% vs 6.4%; P = .01), whereas there was no significant difference in the percentage of hemorrhagic complications (0.5% vs 2.2%; P = .22). In the multivariate analysis, clopidogrel as the antiplatelet medication was the sole significant risk factor for thromboembolism in this series of patients undergoing stent-assisted coil embolization. CONCLUSION: Use of low-dose PSG as an antiplatelet premedication is quick, effective, and safe for stent-assisted coil embolization of unruptured intracranial aneurysms. Prasugrel premedication significantly lowered the frequency of thromboembolic events without increasing the risk of hemorrhage.